(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Among a score of excellent women writers of Indo-Englishfiction, such a Nayantara Sahgal, Anita Desai, Shashi Deshpande, GetaMukherjee, Namita Gokhale and others, Rama Mehta holds a unique place onaccount of her deep insight into the lives, life style, pangs and pride, tears,fears and loyalty towards the family and community tradition of the Rajputwomen of Mewar. They cling to traditionand purdah on one hand and yet compromise with change and modernity on theother. The novel traces theactualization of a Bombay-educated modern woman, Geeta into the Havelitraditions and gradual compromise with the institutions of purdah,child-marriage and female education. Theway Geeta Mehta has minutely described the inside life of the Udaipur havelis,leaves the reader in real sense of awe and revelation.